Pemanfaatan Sumber Daya Lokal untuk Pembuatan Pupuk Organik: Solusi Berkelanjutan bagi Petani dan Masyarakat - Tjilen, Alexander Phuk; Simatupang, David Oscar; Tambaip, Beatus; Riyanto, Pulung (Indra Institute Research & Publication, 2024)
The community service program focused on utilizing local resources for the production of organic fertilizers in Kelurahan Mandala, Merauke District, aims to create sustainable solutions for farmers and the community. The program was conducted from June to August 2024 through various interrelated stages, including socialization, education, technical training, provision of equipment, as well as mentoring and monitoring. The results showed significant impacts in reducing agricultural production costs by replacing expensive imported chemical fertilizers with self-produced organic fertilizers. This cost reduction increased farmers' profit margins and opened new business opportunities. Additionally, the use of organic fertilizers contributed to soil fertility restoration and improved water retention capacity, supporting agricultural ecosystem sustainability and reducing environmental damage risks. The program also successfully enhanced farmers' knowledge and skills in sustainable agricultural technology through training and technical demonstrations. Strengthening the community through farmer groups accelerated the adoption of organic fertilizers and reinforced social solidarity among farmers. The provision of equipment such as composters and shredding machines improved the efficiency of organic fertilizer production, while regulatory support and incentives from the government encouraged the adoption of sustainable agricultural practices. Overall, this program demonstrates that utilizing local resources for organic fertilizer production not only offers a more affordable economic solution but also provides significant environmental and social benefits, creating a strong foundation for more sustainable and competitive agriculture